Study of potential transfer of aluminum to the brain via the olfactory pathway. (February 2018) - Chalansonnet, Monique; Carabin, Nathalie; Boucard, Stéphane; Merlen, Lise; Melczer, Mathieu; Antoine, Guillaume; Devoy, Jérôme; Remy, Aurélie; Gagnaire, François
Highlights: Aluminum salts detected at low levels in the brain after intranasal instillation. Aluminas are not transferred to the brain via the olfactory pathway. No significant lesions in the olfactory mucosa after treatment with aluminas. Abstract: Many employees in the aluminum industry are exposed to a range of aluminum compounds by inhalation, and the presence of ultrafine particles in the workplace has become a concern to occupational health professionals. Some metal salts and metal oxides have been shown to enter the brain through the olfactory route, bypassing the blood-brain barrier, but few studies have examined whether aluminum compounds also use this pathway. In this context, we sought to determine whether aluminum was found in rat olfactory bulbs and whether its transfer depended on physicochemical characteristics such as solubility and granulometry. Aluminum salts (chloride and fluoride) and various nanometric aluminum oxides (13 nm, 20 nm and 40–50 nm) were administered to rats by intranasal instillation through one nostril (10 μg Al/30 μL for 10 days). Olfactory bulbs (ipsilateral and contralateral relative to instilled nostril) were harvested and the aluminum content was determined by graphite furnace atomic absorption spectrometry after tissue mineralization. Some transfer of aluminum salts to the central nervous system via the olfactory route was observed, with the more soluble aluminum chloride being transferred at higher levels than aluminum fluoride. No cerebral translocation of any of the aluminas studied was detected.